Attaining sustainability of industrial production based on environment focused innovations - Bryzhan, I.A.; Lepa, R.M. (Економіка промисловості, 2014)
This paper looks into the need for building up a concept and mechanism of environment focused management of industrial production development. It is critical to start using a concept of environmentally focused development, which has to replace a conventional concept of economic development, based on the extensive consumption of natural resources and great imprint on the environment. Instrumentally innovations are to become one of state regulation subjects within this concept, which will allow bringing the system under regulation into a new development phase. These innovations have to be environmental focused on nature and for mitigating ecodestructive impact, while promoting energy-saving technologies. To secure environmental focused anti-recessionary management of industrial production development the national economy has to adopt a sustainable development model, which can be achieved thorough designing an effective anti-recessionary state policy. The first part of the paper focuses on the theoretical background and overview of research results related to economic development processes of national economy with allowance for the ecological factor. The key element of economy is production; hence, securing a continuous industrial growth is among major issues addressed by economic science. The second part of the paper offers a mechanism of environmentally focused anti-recessionary management of industrial production development which includes seven complementary functional directions: marketing, diagnostics, forecasting, strategic goal-setting, tactical planning, organization and control. Implementation of the proposed mechanism will create sustainability of industrial production due to green innovations.